Decreased numbers of regulatory T cells are associated with human atherosclerotic lesion vulnerability and inversely correlate with infiltrated mature dendritic cells - Dietel, Barbara; Cicha, Iwona; Voskens, Caroline; Verhoeven, Eric; Achenbach, Stephan; Garlichs, Christoph (Atherosclerosis, 2013)
Purpose: Mature dendritic cells (DCs) play a crucial role in the inflammatory process within atherosclerotic lesions by stimulation of effector T cells, which can contribute to plaque instability. Interactions between DCs and regulatory T cells (Treg), which regulate immune response by attenuating acute inflammation, are postulated to be involved in the pathogenesis of autoimmune diseases. We investigated a possible correlation between infiltrated DCs and Treg in human atherosclerotic plaques. Methods: Cross-sections of 40 human carotid endarterectomy specimens were classified into groups of stable and vulnerable plaques using Trichrome staining. Immunohistochemical staining of plaques was used to detect infiltrated total (S100) and mature DCs (fascin, DC-LAMP, CD83), Treg (CD3, Foxp3), and to analyze the inflammatory state of the plaques (CD3, COX-2, CD68). In addition, RNA was isolated from plaque specimens and quantitative real-time PCR was performed to analyze transcription rates of DC markers (CD11c, CD209, HLA-DR), maturation markers (CD80, CD83, CD86), Treg-associated genes (CTLA-4, Foxp3) and of pro- and anti-inflammatory cytokines (TGFβ-family, IL-10, IFN-γ, IL-17α, IL-6). Migration assays and adhesion experiments were performed, to investigate the effects of Treg on mature DCs invitro. Results: As compared with stable plaques, vulnerable lesions were characterized by increased numbers of COX-2-expressing cells and T lymphocytes, indicating an enhanced inflammatory process. In vulnerable plaques, numbers of total and mature DCs were significantly higher in the inflammatory plaque shoulder, whereas the numbers of Treg were decreased compared to stable plaques. This inverse correlation and the association of the observed infiltration rates with plaque stability, were confirmed by PCR analyses, showing increased transcription levels of DC-specific markers, decreased mRNA expression of Treg-associated genes and decreased anti-inflammatory cytokines in vulnerable atherosclerotic plaques. In vitro, pre-incubation of mature DCs with Treg resulted in decreased DC migration and inhibited the adhesion of DCs to endothelial cells under non-uniform shear stress. Conclusions: The results of our study provide novel insights in the direct interaction of mature DCs and Treg in plaque inflammation and stability. © 2013 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Carotid plaques; Dendritic cells; Immunologic tolerance; Regulatory T cells